Legal Protection for Neglected Children Based on Regional Regulation of Bali Province - Ngurah Aldwin Amartya, I Gusti; Ayu Sadnyini, Ida (JURNAL USM LAW REVIEW, 2024)
The aims of this research are to determine legal protection for neglected children based on the regional regulations of Bali Province. The problem in this study is how legal protection for neglected children in the province of Bali is based on the Regional Regulations of Bali Province Number 6 of 2014. This research uses a normative legal method by taking a statutory approach. The sources of legal materials used are primary and secondary, which are reviewed using literature study techniques and analyzed descriptively and qualitatively. The result can be seen that legal protection for neglected children based on Article 2 of Regulation Number 6 of 2014 of Bali Province concerning child protection states that every child has the right to be able to live, grow, develop, and participate appropriately following human dignity. Preventive protection is also emphasized, where the state, government, local government, community, family, and parents or guardians are obliged and entirely responsible for child protection. This protection is based on the principles of child protection, namely the principle of non-discrimination, the principle of the child's best interests, the right to live, grow, and develop, and the principle of children's participation.